Metasurface-Based Optical Analog Computing: From Fundamentals to Applications - Dingyu Xu; Shuangchun Wen; Hailu Luo (Advanced Devices & Instrumentation)
With unprecedented growth in data information over the past few decades, it is critically important to seek a faster and more efficient method to simplify data processing. In recent years, optical analog computing provides an available way due to its large capacity, energy saving, and high efficiency. Metasurfaces, as 2-dimensional artificial nanostructures, have shown an extraordinary ability for controlling light and paving a pathway toward all-optical analog computing. In this brief review, we discuss the latest development in metasurface-based optical analog computing. Theoretical fundamentals and experimental demonstrations of optical analog computing for resolving a variety of mathematical problems have been reviewed, including differential operation, convolution operation, and Fourier transformation. Finally, a brief introduction of emerging applications in microscopy imaging, quantum imaging, and holographic imaging is presented.